2022
DOI: 10.14246/irspsd.10.4_174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Global Urban Grid on Natural Movement within a Local Public Space

Abstract: An urban centre acts as the interface of economic activities and people and represents diversity, which can grow or decline over time. Here, we review the literature to explain the factors supporting and obstructing urbanisation based on three theories on urban morphology: theory of natural movement, theory of movement economy and theory of spatial centrality. Two research questions were then formulated to explain the morphological logic of urbanisation and the influence of the global movement grid on local na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…This would facilitate the circulation of people and the continuous distribution of various activities (Rattanathavorn, Paksukcharern, & Peerapun, 2013). Thinnakorn & Chanklap (2022) studied the characteristics of the urban grid in the old town district of Nakhon Si Thammarat, Thailand, to explain the factors contributing to the current deterioration of the old town. The research found that, firstly, the old town had a concentration of negative attractors, primarily religious and government land use, which hindered the movement economy.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…This would facilitate the circulation of people and the continuous distribution of various activities (Rattanathavorn, Paksukcharern, & Peerapun, 2013). Thinnakorn & Chanklap (2022) studied the characteristics of the urban grid in the old town district of Nakhon Si Thammarat, Thailand, to explain the factors contributing to the current deterioration of the old town. The research found that, firstly, the old town had a concentration of negative attractors, primarily religious and government land use, which hindered the movement economy.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The research found that, firstly, the old town had a concentration of negative attractors, primarily religious and government land use, which hindered the movement economy. This resulted in a shift of the city's center to areas with higher accessibility (Thinnakorn, Chanklap, 2022). Lv, Wang, & Huang (2023) examined the ancient town of Xixing, a canal town that used to be a center for trade in the east Zhejiang Province, China.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This is an application of space syntax to the practice of urban design (Zaleckis, Chmielewski et al, 2022). Thinnakorn and Chanklap (2022) argued that Local public spaces must be designed to support the global movement grid, provided by natural movement and influenced by the global morphological structure. The study was carried out using Space Syntax in Nakhon Si Thammarat Old Town; the results demonstrated a direct influence of the spatial configuration of the global movement grid on urbanization and local natural movement.…”
Section: Using Space Syntax In Explaining Walkabilitymentioning
confidence: 99%